2020
DOI: 10.1007/s12210-020-00930-w
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements (REE) in biology and medicine

Abstract: This survey reports on topics that were presented at the workshop on "Challenges with Rare Earth Elements. The Periodic Table at work for new Science & Technology" hold at the Academia dei Lincei in November 2019. The herein reported materials refer to presentations dealing with studies and applications of rare earth elements (REE) in several areas of Biology and Medicine. All together they show the tremendous impact REE have in relevant fields of living systems and highlight, on one hand, the still existing k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…1). Although not used in our current ovarian mass cytometry studies, isotopes of cadmium, platinum, ruthenium, osmium, and tellurium have been used for antibody labeling and barcoding [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1). Although not used in our current ovarian mass cytometry studies, isotopes of cadmium, platinum, ruthenium, osmium, and tellurium have been used for antibody labeling and barcoding [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, from 238 U isotope to the 252 No isotope, the addition of 10 protons and 4 neutrons reduces T ½ by a factor 10 16 . Further studies on rare earth have been reported in (Ascenzi et al 2020).…”
Section: The Survival Of the Elementsmentioning
confidence: 98%
“…REEs play a vital role also in electrical and electronic equipment such as mobile phones, hard disk drives and fluorescent and LED lamps (Balaram, 2019), defense applications (Mancheri et al, 2013), Catlaysts (Schmid, 2019), high tech (e.g. Haxel et al, 2002) and pharmaceuticals and medicine (Ascenzi et al, 2020). Presence of REEs in living systems and their mobilisation could be used to design niche diagnostic procedures (Ascenzi et al, 2020), though this is still very much in its infancy.…”
Section: Introductionmentioning
confidence: 99%